Avelumab first-line maintenance treatment in patients with locally advanced or metastatic urothelial carcinoma: real-world results from a Korean expanded access program - Park, Se Hoon; Shin, Sang Joon; Rha, Sun Young; Beom, Seung-Hoon; Seo, Ho Kyung; Keam, Bhumsuk; Kim, Miso; Hong, Yoon-Hee; Yoon, Shinkyo; Lee, Jae-Lyun (Frontiers in Oncology, 2024)
Background: The JAVELIN Bladder 100 phase 3 trial demonstrated the efficacy and safety of avelumab administered as first-line (1L) maintenance treatment in patients with advanced urothelial carcinoma (UC) without disease progression after 1L platinum-based chemotherapy. This study provides the first real-world data from Korea regarding avelumab 1L maintenance treatment, which were obtained from a nationwide expanded access program (EAP).Methods: This open-label EAP was conducted at five centers from September 2021 until June 2023. Eligible patients had unresectable locally advanced or metastatic UC and were progression free after 1L platinum-based chemotherapy. Patients received avelumab 10 mg/kg intravenously every 2 weeks per local prescribing information. Safety and effectiveness were assessed by treating physicians according to routine practice.Results: Overall, 30 patients were enrolled. At initial UC diagnosis, 20 patients (66.7%) had stage 4 disease and 12 (40.0%) had visceral metastases. The most common 1L chemotherapy regimen was gemcitabine + cisplatin (21 patients; 70.0%). All but one patient (96.7%) had received 4-6 cycles of 1L chemotherapy. The median interval from end of 1L chemotherapy to start of avelumab was 4.4 weeks. Median duration of avelumab treatment was 6.2 months (range, 0.9-20.7); nine patients (30.0%) received >12 months of treatment. Adverse events related to avelumab occurred in 21 patients (70.0%) and were grade ≥3 or classified as serious in three patients (10.0%). Median progression-free survival was 7.9 months (95% CI, 4.3-13.1). Overall survival was not analyzed because only one patient died.Results from this EAP demonstrate the clinical activity and acceptable safety of avelumab 1L maintenance treatment in Korean patients with advanced UC, consistent with previous studies.